2019
DOI: 10.1002/cpdd.665
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1, Open‐Label, Pharmacokinetic Trial to Investigate Possible Drug‐Drug Interactions Between Clobazam, Stiripentol, or Valproate and Cannabidiol in Healthy Subjects

Abstract: GW Pharmaceuticals’ formulation of highly purified cannabidiol oral solution is approved in the United States for seizures associated with Lennox‐Gastaut and Dravet syndromes in patients aged ≥2 years, for which clobazam, stiripentol, and valproate are commonly used antiepileptic drugs. This open‐label, fixed‐sequence, drug‐drug interaction, healthy volunteer trial investigated the impact of cannabidiol on steady‐state pharmacokinetics of clobazam (and N‐desmethylclobazam), stiripentol, and valproate; the reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
182
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(199 citation statements)
references
References 37 publications
9
182
1
1
Order By: Relevance
“…The effects reported on BRV here may trigger additional studies on pharmacokinetic interactions of CBD and coapplied AEDs. Coadministration of CLB and CBD leads not only to an increase of d ‐CLB but also to an increase of CBD itself . Because we did not measure CBD levels in our study, the question of bidirectional BRV‐CBD interaction remains open.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The effects reported on BRV here may trigger additional studies on pharmacokinetic interactions of CBD and coapplied AEDs. Coadministration of CLB and CBD leads not only to an increase of d ‐CLB but also to an increase of CBD itself . Because we did not measure CBD levels in our study, the question of bidirectional BRV‐CBD interaction remains open.…”
Section: Discussionmentioning
confidence: 93%
“…However, data on drug‐drug interactions in humans are limited to a few antiepileptic drugs (AEDs). Previous trials observed a relevant interaction of clobazam (CLB) and CBD, often associated with increased sedation but also possibly contributing to improvement of seizure control …”
Section: Introductionmentioning
confidence: 99%
“…The pharmacokinetics (PK) of CBD have been described in several recent studies, both in patients with epilepsy and in healthy volunteers . In one healthy volunteer trial, after single CBD doses of between 1500 and 6000 mg, CBD appeared rapidly in plasma; maximum observed plasma concentration (C max ) occurred between 3 and 5 hours postdose, and CBD remained detectable up to 72 hours postdose .…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Cannabidiol doses of 20 mg/kg/day (or 1500 mg/day) increased the exposure of Ndesmethylclobazam with a mean of 6-fold (95% CI of the median fold-increase of 1.9-7.01 at week 4 and 2.17-6.33 at week 8) in children with refractory epilepsy despite clobazam dose reductions, 17 with 3-fold in adults with epilepsy 18 and with 3.4-fold in healthy subjects. 19 Cannabidiol doses of 5, 10 and 20 mg/kg/day resulted in a mean increase of N-desmathylclobazam of 3.6, 2.7 and 3.3-fold, respectively, in children with Dravet syndrome. 20 Data from the 2 trials in patients with Lennox-Gastaut and 1 trial in patients with Dravet syndrome moreover showed that respectively 49%, 48% and 66% of the patients taking cannabidiol during the studies, were taking clobazam as a concomitant antiepileptic drug.…”
mentioning
confidence: 93%
“…Previous studies identified significant drug–drug interactions between cannabidiol and other antiepileptic drugs, such as topiramate, eslicarbazepine, zonisamide, rufinamide and N‐desmethylclobazam, the active metabolite of clobazam . Cannabidiol doses of 20 mg/kg/day (or 1500 mg/day) increased the exposure of N‐desmethylclobazam with a mean of 6‐fold (95% CI of the median fold‐increase of 1.9–7.01 at week 4 and 2.17–6.33 at week 8) in children with refractory epilepsy despite clobazam dose reductions, with 3‐fold in adults with epilepsy and with 3.4‐fold in healthy subjects . Cannabidiol doses of 5, 10 and 20 mg/kg/day resulted in a mean increase of N‐desmathylclobazam of 3.6, 2.7 and 3.3‐fold, respectively, in children with Dravet syndrome .…”
Section: Introductionmentioning
confidence: 99%